Modulating Gene Expression (IntechOpen, 2023)
RNA interference (RNAi) is a widely used technology for gene silencing and has become a key tool in a myriad of research and lead discoveries. In recent years, the mechanism of RNAi agents has been well investigated, and the technique has been optimized for better effectiveness and safety. On the other hand, the clustered regularly interspaced short palindromic repeats (CRISPR)-associated Cas9/gRNA system is a recent, novel, targeted genome-editing technique derived from the bacterial immune system. Recent advances in gene-editing research and technologies have enabled the CRISPR Cas9 system to become a popular tool for sequence-specific gene editing to correct and modify eukaryotic systems. In this book, we will focus on the mechanisms, applications, regulations (their pros and cons), and various ways in which RNAi-based methods and CRIPSR-Cas9 technology have stimulated the modulation of gene expression, thereby making them a promising therapeutic tool to treat and prevent complex diseases and disorders.